Use of state force, neoconstitutionalism and promotion of a communicative reason - Castañeda Quitian, Pedro Elías (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The main objective of this article is to relate Habermas's concepts of communicative reason and deliberative democracy with the constitutional principles that should guide the use of force by law enforcement officials, in order to highlight responsibility state in terms of promoting a context in which human rights and the search for the common good are the guiding axes. The method used is the theoretical and descriptive analysis of concepts, taking into account a critical perspective of human rights and the legal parameters that should guide the use of force by state agents. As a result, the conclusion is reached that the State should not only promote protocols for the use of force at the legal level, but also promote a communicative reason, that is, a mutual understanding based on agonism and not on antagonism. so that, in this way, despite the different positions that different social groups may have, it is possible to have the common good as a goal and the construction of peaceful social contexts where the need to use force is lessened.